Belarus Country Gender Profile, 2016 Update - World Bank Group (World Bank, Washington, DC, 2018)
Gender equality is a core development objective in its own right, and it is also a smartdevelopment policy. Gender equality is also a key pathway to ensure lasting poverty reductionand shared prosperity. This update to the ‘2013 Belarus Country Gender Profile’ seeks to identifywhere progress has been achieved in terms of increasing opportunities for women and men inBelarus since that last assessment and where further policy action is required. As such, itunderstands gender equality to mean the closing of the gaps between women and men in areasthat are critical for them to access and take advantage of existing opportunities namelyendowments such as health and education; economic opportunities, via access to labor, land andfinancial markets;, and agency, including norms, representation, and freedom of violence (WorldBank 2016). Overall, Belarus’ ranges better than many countries in terms of gender equality. Thecountry’s gender gaps are much smaller than those observed in other countries in the region andthe world. The country ranks 30 among the 144 countries covered by the 2016 World EconomicForum Global Gender Gap Index, largely due to its good results on education outcomes and theirreflection in the labor market—Belarus ranks number 1 in terms of female enrollment in all levelsof education and also when it comes to having female professional and technical workers, and forwomen to enjoy a healthy life expectancy. However, these results are muted by the pervasivegender wage gap observed in Belarus, leaving the country at place 54 in the global ranking andthe low representation of women in political positions. While the country is among the top thirdof countries when it comes to parliamentary representation –ranks 47 among the 144 countrieswith a female parliamentary representation of 27 percent, it ranks 108 when it comes to the shareof women in ministerial positions, with an overall ranking of 80 for political empowerment.